We came to welcome you : a novel of suburban horror - Tirado, Vincent (William Morrow, 2024)
"The Other Black Girl meets Midsommar in this spine-chilling, propulsive psychological adult debut from highly acclaimed author Vincent Tirado, in which a married couple moves into a gated "community" that slowly creeps into a pervasive dread akin to the social horror of Jordan Peele and Lovecraft County-We Came to Welcome You cleverly uses the uncanny to illuminate the cultish, shocking nature of systemic racism. Where beauty lies, secrets are held...ugly ones. Sol Reyes has had a rough year. After a series of workplace incidents at her university lab culminates in a plagiarism accusation, Sol is put on probation. Dutiful visits to her homophobic father aren't helping her mental health, and she finds her nightly glass of wine becoming more of an all-day-and all-bottle-event. Her wife, Alice Song, is far more optimistic. After all, the two finally managed to buy a house in the beautiful, gated community of Maneless Grove. However, the neighbors are a little too friendly in Sol's opinion. She has no interest in the pushy Homeowners Association, their bizarrely detailed contract, or their never-ending microaggressions. But Alice simply attributes their pursuit to the community motto: "Invest in a neighborly spirit"...which only serves to irritate Sol more. Suddenly, a number of strange occurrences-doors and stairs disappearing, roots growing inside the house-cause Sol to wonder if her social paranoia isn't built on something more sinister. Yet Sol's fears are dismissed as Alice embraces their new home and becomes increasingly worried instead about Sol's drinking and manic behavior. When Sol finds a journal in the property from a resident that went missing a few years ago, she realizes why they were able to buy the house so easily... Through Sol's razor-sharp tongue and macabre sense of humor, Tirado explores the very real pressures to assimilate with one's surroundings to "survive," while also asking the question: Is it survival when you're no longer your true self? Because in Maneless Grove, either you become a good neighbor-or you die"--